1999
DOI: 10.1046/j.1365-2788.1999.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset of dementia and age of menopause in women with Down’s syndrome

Abstract: Menstrual status and the age of menopause were investigated in 143 Irish females with Down's syndrome (DS). The average age of menopause in 42 subjects (44.7 years) was younger than in the general population. The age at onset of dementia correlated with the age of menopause. This finding may be a manifestation of accelerated ageing in DS or point to oestrogen deficiency being an independent risk factor for the development of Alzheimer's dementia in DS. The implications of this finding for possible treatments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 19 publications
1
37
1
2
Order By: Relevance
“…One previous study found a correlation between age at menopause and onset of AD in women with DS, 35 but the number of dementia cases was low and supporting hormonal data were not available. In addition, the presence of the apolipoprotein E (ApoE) ε4 allele is associated with earlier age at onset and increased risk of AD in adults with and without DS.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…One previous study found a correlation between age at menopause and onset of AD in women with DS, 35 but the number of dementia cases was low and supporting hormonal data were not available. In addition, the presence of the apolipoprotein E (ApoE) ε4 allele is associated with earlier age at onset and increased risk of AD in adults with and without DS.…”
mentioning
confidence: 86%
“…In keeping with convention, we classified age at natural menopause as the age at the last menstrual period preceding cessation of menses for 12 months, in the absence of known causes of amenorrhea (eg, surgery). The median age at menopause was 46.0 years (range, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. For analysis of AD risk associated with age at menopause, we split at the median to classify women as experiencing "early" (Յ46 years) or "late" (Ͼ46 years) age at menopause.…”
Section: Classification Of Age At Menopausementioning
confidence: 99%
“…In females with Down's syndrome, the average age of menopause (44.7 yr; n ϭ 42) is younger than in the general population, and onset of dementia correlates with the age of menopause (440). The results of a multicenter clinical trial in women with established AD showed that estrogen treatment for 12 months did not halt the decline in cognitive function (441), but the average age of the women studied was 75 yr; and it remains to be determined whether younger women would benefit.…”
Section: Estradiol and Admentioning
confidence: 98%
“…Some investigators do not report beneficial effects of estrogen in any memory tasks in women with AD (Mulnard et al, 2000), leaving this important question unresolved to date. Estradiol treatment has not been tested in elderly women with DS, even though they are twice as likely to undergo early menopause than non-DS women (Carr and Hollins, 1995;Schupf et al, 1997;Cosgrave et al, 1999) and show a decline in cognitive function linked to menopause (Patel et al, 2001). Estradiol modifies the function and morphology of hippocampal neurons in situ and in tissue culture.…”
Section: Introductionmentioning
confidence: 99%